2019
DOI: 10.1136/jech-2018-211006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating effects of Uber ride-sharing service on road traffic-related deaths in South Africa: a quasi-experimental study

Abstract: BackgroundRoad traffic deaths are a substantial barrier to population health improvement in low-income and middle-income countries (LMICs). In South Africa, the road-traffic injury mortality (RTM) rate of 27 per 100 000 population is twice the global average, over 60% of which are alcohol-related. Recent US studies suggest the Uber ride-sharing service may reduce alcohol-related RTM, however RTM burden in the USA is relatively low and transport behaviours differ from LMICs.MethodsUsing certification data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…On the contrary, and after analyzing data on traffic accident causalities associated with alcohol consumption in the 100 largest metropolitan areas of the United States between 2005 and 2014, no relationship was found between these deaths and the implementation of these services [11]. Similarly, Huang et al [12] analyzed data for some South African cities and found no evidence of reduction in accident rate after the introduction of Uber.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, and after analyzing data on traffic accident causalities associated with alcohol consumption in the 100 largest metropolitan areas of the United States between 2005 and 2014, no relationship was found between these deaths and the implementation of these services [11]. Similarly, Huang et al [12] analyzed data for some South African cities and found no evidence of reduction in accident rate after the introduction of Uber.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review suggested that designated driver programmes were not found to be effective in decreasing alcohol-related traffic outcomes. 9 Research has also assessed the effects of network ridesharing on accidents, [10][11][12][13][14][15][16] with six studies [10][11][12][13][14][15] looking at the association between network ridesharing and alcohol-impaired driving in the United States (US). Results are mixed, with Martin-Buck, 12 Greenwood and Wattal, 13 Peck 14 and Morrison et al 15 showing reductions in alcoholrelated crashes after Uber was introduced, whereas Brazil and Kirk 10 and Dills and Mulholland 11 did not observe any change in these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A second limitation is related to the U.S.-centric focus of our study. To date, there has been very little research on the association between ridehailing and traffic fatalities focused on countries besides the United States (the few exceptions include recent studies of Chile, Great Britain, and South Africa), yet two of Uber's top five markets (London and Sao Paulo) are not in the United States and the majority of ridehailing trips worldwide occur outside of the United States, with an estimated 70 percent in Asia alone [25][26][27][28]. Hence, future research will need to examine the association between ridehailing and traffic fatalities beyond the United States before a full accounting of the impacts of ridehailing can be determined.…”
Section: Plos Onementioning
confidence: 99%